Effectiveness of Digital-Based Islamic Religious Education in Society 5.0 - Jamalullel, Jamalullel; Nasehudin, Nasehudin (LifeSciFi, 2025)
This study aims to examine the effectiveness of digital based Islamic Religious Education learning in the Society 5.0 era through a case study at MTs Al Falah Jatirokeh. Digital learning is implemented using platforms such as Google Classroom, Zoom, YouTube, and other interactive media to deliver Islamic material visually and contextually. The study used a qualitative approach with a case study method. Data collection techniques included observation, in depth interviews, and documentation. The results show that the effectiveness of digital learning is greatly influenced by teacher and student readiness, the use of appropriate technological media, and active student participation. Teachers who master digital pedagogy have been shown to improve students' understanding of abstract materials such as monotheism and morals through visual media. Generation Z students have shown a positive response to flexible and interactive learning. However, challenges remain, such as limited devices and stable internet access. Therefore, support from madrasah and government policies is needed to equitably distribute facilities and provide digital literacy training. Digital based Islamic Education learning has been proven to make a positive contribution to the quality of Islamic education which is more adaptive, innovative, and relevant in the digital era.